Maximum ground level concentration Of air pollutant (MAUSAM, 1991)
The emission of an air pollutant from an elevated point source according to Gaussian plume model has been presented. Au. elementary theoretical treatment for both the highest possible ground-level concentration and the downwind distance at which this maximum occurs for different stability classes has been constructed. The effective height release modification was taken into consideration. An illustrative case study, namely, the emission from the research reactor in Inchas, has been studied. The results of these analytical treatments and of the derived semi-empirical formulae are discussed and presented in few  illustrative diagrams.